1996
DOI: 10.1021/om950972t
|View full text |Cite
|
Sign up to set email alerts
|

CO Insertion of (η3-allyl)Fe(CO)2(NO) Complexes by Diphosphines

Abstract: Allyl groups of (η3-allyl)Fe(CO)2(NO) complexes undergo regioselective cabonylation at the less substituted carbon of the η3-allyl ligands in the presence of 1,2-bis(diphenylphosphino)ethane to give (β,γ-unsaturated acyl)Fe(CO)(NO)(dppe) complexes in good yields. X-ray analysis of the acyl complex thus obtained revealed that the complex has a trigonal bipyramid geometry. A characteristic substituent effect of the η3-allyl ligands on the CO insertion reaction was observed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

1997
1997
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…Our reactivity studies have shown [Fe 2 (CO) 6 (μ-PPh 2 ){μ-η 1 :η 2 α,β -(H)C α C β C γ H 2 }] ( 1 ) to be highly reactive toward protic and aprotic nucleophiles; primary, secondary, and tertiary phosphines all react regiospecifically at C α while primary amines react at CO and/or C β of the allenyl ligand. , We have now found that alkyllithium reagents react with 1 , via a highly selective nucleophile−carbonyl−allenyl coupling sequence, to give the β,γ-unsaturated carbonyl compounds [Fe 2 (CO) 5 {P(OMe) 3 }(μ-PPh 2 )(μ-η 1 :η 2 -{RC(O)CH 2 }CCH 2 )] (R = Me, Et, n Bu, C 4 H 3 S). Until now, β,γ-unsaturated carbonyl compounds have typically been synthesized using mononuclear iron complexes of unsaturated hydrocarbyl ligands, for example, direct nucleophilic attack of R - on a coordinated vinylketone, bis(diphenylphosphino)methane-induced migration of CO into an η 3 -allyl ligand, and reaction of organic electrophiles with the anionic allyl complex [(η 3 -allyl)Fe(CO) 3 ] - …”
Section: Resultsmentioning
confidence: 86%
“…Our reactivity studies have shown [Fe 2 (CO) 6 (μ-PPh 2 ){μ-η 1 :η 2 α,β -(H)C α C β C γ H 2 }] ( 1 ) to be highly reactive toward protic and aprotic nucleophiles; primary, secondary, and tertiary phosphines all react regiospecifically at C α while primary amines react at CO and/or C β of the allenyl ligand. , We have now found that alkyllithium reagents react with 1 , via a highly selective nucleophile−carbonyl−allenyl coupling sequence, to give the β,γ-unsaturated carbonyl compounds [Fe 2 (CO) 5 {P(OMe) 3 }(μ-PPh 2 )(μ-η 1 :η 2 -{RC(O)CH 2 }CCH 2 )] (R = Me, Et, n Bu, C 4 H 3 S). Until now, β,γ-unsaturated carbonyl compounds have typically been synthesized using mononuclear iron complexes of unsaturated hydrocarbyl ligands, for example, direct nucleophilic attack of R - on a coordinated vinylketone, bis(diphenylphosphino)methane-induced migration of CO into an η 3 -allyl ligand, and reaction of organic electrophiles with the anionic allyl complex [(η 3 -allyl)Fe(CO) 3 ] - …”
Section: Resultsmentioning
confidence: 86%
“…Complexes of the form (η 3 -allyl)Fe(CO) 2 (NO) are generated by the reactions of [Fe(CO) 3 (NO)] - with allyl halides or allyl transmetalation reagents such as [(η 3 -allyl)PdX)] 2 . The η 3 -allyl ligands in these nitrosyl complexes react with both carbon- and nitrogen-based electrophiles and nucleophiles and thus serve as synthetically equivalent synthons for carboanions and carbocations. , …”
Section: 12 Organometallic Complexesmentioning
confidence: 99%
“…As summarized in Scheme , (η 3 -allyl)Fe(CO) 2 (NO) undergoes displacement of a carbonyl ligand by phosphines and phosphites (L) to form (η 3 -allyl)Fe(CO)(L)(NO) . In contrast, reaction with bidentate phosphines such as diphenylphosphinoethane (dppe) causes regioselective insertion of a carbonyl ligand into the less-substituted Fe−C σ-bond of the η 1 ,η 2 -allyl resonance form resulting in (R 1 R 2 CCR 3 C(O))Fe(CO)(dppe)(NO). , Interestingly, the η 3 -cyclopropenyl analogues of these systems, (η 3 -C 3 Ph 3 )Fe(CO) 2 (NO), react with P n Bu 3 to generate both the carbonyl-substituted complex (η 3 -C 3 Ph 3 )Fe(CO)(P n Bu 3 )(NO) and the product of CO insertion (η 3 -C 3 Ph 3 CO)Fe(CO)(P n Bu 3 )(NO) . The neutral acyl dicarbonyl nitrosyl complexes, (RC(O))Fe(CO) 2 (NO), react with allenes to form η 3 -allyl complexes which have acyl groups at the central carbon of the allylic ligands …”
Section: 12 Organometallic Complexesmentioning
confidence: 99%
See 1 more Smart Citation